Applying metagenomics to structural and functional analyses of microbial communities from lagoon sediments in some provinces of central Vietnam - Tran Thi Hong; Ngo Van Anh; Nguyen Thi Ngoc Anh; Nguyen Van Phuong (Novel Research in Microbiology Journal)
Metagenomics is an important technique for discovering and screening significant bioactive compounds such as polyketide synthases, non-ribosomal peptide synthetases, antibiotics, and biocatalysts. The enormous potential of microbial diversity in coastal lagoons remains untapped because of the difficulty of culturing many microorganisms under laboratory conditions. Therefore, this study aimed to decipher the structural and functional diversity of microbial communities, including un-culturable species in lagoon sediments collected from Tam Giang, Nai, and Thi Nai lagoons, which were located in the central coast of Vietnam using metagenomics approach. The results showed that all three large lagoons exhibited a high diversity of fungal species among the eukaryotic species and a high diversity of bacterial and archaeal species. Among them, the most prominent phyla included Ascomycota (fungal phyla), Firmicutes and Proteobacteria (bacterial phyla), and Thaumarchaeota (archaeal phyla). Sequencing of the metagenome samples of microbiome in the three lagoons of Tam Giang, Nai, and Thi Nai using shotgun sequencing technology revealed the existence of 126 potential gene sequences from the Tam Giang lagoon, 346 sequences from the Nai lagoon, and 341 sequences from the Thi Nai lagoon. These sequences participated in various metabolic processes and belonged to more than 30 groups of biologically active compounds. Most of these genes were related to antibacterial, antifungal, antiviral, cancer cell inhibition, and antioxidant activities. This is the first study conducted on lagoon microorganisms in Vietnam, opening up prospects and potential in exploiting microorganisms and biologically active substances with important applications in life from the lagoon ecosystems of Vietnam in particular and the overall world in general.